New insights on neurotransmitters signaling mechanisms in plants. (2nd June 2020) - Akula, Ramakrishna; Mukherjee, Soumya
ABSTRACT: Neurotransmitters (NTs) such as acetylcholine, biogenic amines (dopamine, noradrenaline, adrenaline, histamine), indoleamines [(melatonin (MEL) & serotonin (SER)] have been found not only in mammalians, but also in diverse living organisms-microorganisms to plants. These NTs have emerged as potential signaling molecules in the last decade of investigations in various plant systems. NTs have been found to play important roles in plant life including-organogenesis, flowering, ion permeability, photosynthesis, circadian rhythm, reproduction, fruit ripening, photomorphogenesis, adaptation to environmental changes. This review will provide an overview of recent advancements on the physiological and molecular mechanism of NTs in plants. Moreover, molecular crosstalk of SER and MEL with various biomolecules is also discussed. The study of these NTs may serve as new understanding of the mechanisms of signal transmission and cell sensing in plants subjected to various environmental stimulus.